Pembuatan Asap Cair, Biochar, dan Arang Aktif dengan Alat Pirolisis Detachable pada Rintisan Teaching Factory Pembibitan Politeknik Negeri Jember - Harlianingtyas, Irma; Sugiyarto, Sugiyarto; Triwidiarto, Cherry; Supriyadi, Supriyadi (Politeknik Negeri Jember, 2023)
The problem of land fertility on the Jember State Polytechnic land is an important matter to be addressed, so there is a need for land rehabilitation to maintain land fertility. Politeknik Negeri Jember has an abundance of agricultural waste such as coconut shells, coffee shells, cocoa shells, rice husks and corn cobs which have the potential to be used as organic products that are beneficial for land fertility. Based on this, the community service implementation team proposes to provide a solution by utilizing agricultural waste into biochar, bio-oil and activated charcoal products which play a role in soil fertility. The proposing team together with the management of the Nursery Teaching Factory pilot agreed to make a pyrolysis tool to produce biochar, bio-oil and activated charcoal which functions for land rehabilitation. The service activity began with a Forum Group Discussion (FGD) between the proposing team and the TeFa Nursery management to agree on determining the SOP for product manufacture, location and equipment maintenance. The proposing team also provides assistance in testing product content, packaging, product legality, and product marketing for program sustainability. After this activity, it is hoped that there will be income from product sales, additional investment in equipment, and management of agricultural waste raw materials.